The Medical Properties of Iris and its Usage in Pharmaceutical, Perfumery and Cosmetic Industries - Oztas, Fulya; Turkmen , Aysun; Oztas, Haydar; Turkmen, Mustafa (Medical Research and Its Applications Vol. 4, 2024)
Studies have revealed that around 30 iris species are used for different purposes in traditional medicine. The fresh roots of Iris pseudacorus species have vasoconstrictor, toothache-reducing, cathartic, emetic, emmenagogue and odontalgic properties. Its use as an ornamental plant in different societies since ancient times. Rhizomes of the plant have been defined as the medicinal parts, and they contain medicinally large amounts of secondary metabolites and plant extracts are mostly taken orally and their topical use is common. From past to present, different types of this plant have increased their popularity in the perfume and cosmetic industry due to their sweet aromas. The phytochemical properties of iris species have shown the presence of various bioactive compounds belonging to different classes, including alkaloids, flavonoids and their derivatives, quinones, terpenes, steroids and simple phenolics Bioactive properties of iris extracts have shown that the phytocomponents in the plant have antioxidant, anticarcinogenic, antimitagenic and antimicrobial activities. Some extracts obtained from the plant have significant antifungal and antibacterial properties, especially against bacteria and fungi that cause food poisoning. In addition, iris components are known to have strong antioxidant properties. All these properties support the potential use of iris-based extracts in food products to extend the shelf life of foodstuffs and as flavoring agents. In conclusion, the antioxidant and radical scavenging activities as well as anti-inflammatory properties of extracts of aerial parts and rhizomes of Iris species confirm the traditional and modern medicinal use of this plant.